Engineering Nanowire-Mediated Cell Lysis for Microbial Cell Identification - Takao Yasui; Takeshi Yanagida; Taisuke Shimada; Kohei Otsuka; Masaki Takeuchi; Kazuki Nagashima; Sakon Rahong; Toyohiro Naito; Daiki Takeshita; Akihiro Yonese; Ryo Magofuku; Zetao Zhu; et al. (My University, 2019)
Researchers have demonstrated great promise for inorganic nanowire use in analyzing cells or intracellular components. Although a stealth effect of nanowires toward cell surfaces allows preservation of the living intact cells when analyzing cells, as a completely opposite approach, the applicability to analyze intracellular components through disrupting cells is also central to understanding cellular information. However, the reported lysis strategy is insufficient for microbial cell lysis due to the cell robustness and wrong approach taken so far (i.e., nanowire penetration into a cell membrane). Here we propose a nanowire-mediated lysis method for microbial cells by introducing the rupture approach initiated by cell membrane stretching; in other words, the nanowires do not penetrate the membrane, but rather they break the membrane between the nanowires. Entangling cells with the bacteria-compatible and flexible nanowires and membrane stretching of the entangled cells, induced by the shear force, play important roles for the nanowire-mediated lysis to Gram-positive and Gram-negative bacteria and yeast cells. Additionally, the nanowire-mediated lysis is readily compatible with the loop-mediated isothermal amplification (LAMP) method because the lysis is triggered by simply introducing the microbial cells. We show that an integration of the nanowire-mediated lysis with LAMP provides a means for a simple, rapid, one-step identification assay (just introducing a premixed solution into a device), resulting in visual chromatic identification of microbial cells. This approach allows researchers to develop a microfluidic analytical platform not only for microbial cell identification including drug- and heat-resistance cells but also for on-site detection without any contamination.
Keywords: Identification; Microfluidic and Bio-sensing Technologies